2018
DOI: 10.1080/10826084.2018.1508299
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Online-Only Friends on the Substance Use of Young Adults with a History of Childhood Maltreatment

Abstract: Background: Existing research shows that having offline friends that use substances increases risk for individual substance use in adolescence. However, there is little research examining the influence of online social networks on substance use in young adulthood. Objectives: The present study examined the number of online-only Facebook friends (i.e., those with no in-person contact) that were substance users in relation to the participants’ alcohol and marijuana use in the past year. Methods: The sample (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We also examined predictors of substance use in online interactions and found that online-only friends potentially influence offline behavior. Specifically, having a higher number of online-only friends who were substance users was associated with higher substance use in our participants (Negriff, 2019b). Clearly, further examination of online contexts is integral to creating a more complete understanding of the various influences on risk behavior.…”
Section: Summary Of Research Findings To Datementioning
confidence: 88%
“…We also examined predictors of substance use in online interactions and found that online-only friends potentially influence offline behavior. Specifically, having a higher number of online-only friends who were substance users was associated with higher substance use in our participants (Negriff, 2019b). Clearly, further examination of online contexts is integral to creating a more complete understanding of the various influences on risk behavior.…”
Section: Summary Of Research Findings To Datementioning
confidence: 88%
“…In all cases, online peer influence was of lesser magnitude than traditional (face-to-face) peer influence. Another study has similarly failed to find support for unique influence by online-only friends on marijuana use (Negriff, 2019).…”
Section: Unique Online Influences?mentioning
confidence: 99%
“…Additionally, most prior work has been unable to test for the unique effect of one's collective online group, meaning restricting focus to peers who have never been met in person omits part of the cyber context (e.g., offline weak ties who become intimate online friends) and examining online peers as a whole ignores the fact that many adolescents befriend people online who are the same friends offline. In one of the few studies isolating unique online effects, Negriff (2019) initially found a strong association between online-only friends who smoke marijuana and self-reported substance use; however, this association disappeared after controlling for offline friends. Finally, controlling for temporal ordering can help ensure the validity of the findings.…”
Section: Offline Consequences Of Online Socializationmentioning
confidence: 99%